0378 Daytime PAP Accommodation: A Breath of Fresh Air. (25th May 2022) - Newitt, Jennifer; Holmes, William; Strollo, Patrick
Abstract: Introduction: Rising healthcare costs and resource utilization represents a growing problem in the United States, especially for individuals with progressive neuromuscular disorders. Diagnosis and treatment of obstructive sleep apnea has been demonstrated to decrease healthcare resources in the general population; however, there is no well-defined approach to diagnosis and management of sleep-disordered breathing (SDB) in patients with neuromuscular disease (NMD). Many providers believe it best to diagnose and introduce positive airway pressure (PAP) support during a single overnight in-laboratory sleep study. Patients with NMD require a team with understanding of sleep physiology, complex pulmonary pathophysiology, disease process and progression, and advanced PAP therapy modes and indications. Optimal treatment requires patient and caregiver education, frequent monitoring of PAP data, ongoing evaluation of oxygenation and ventilation parameters, as well as assistance with device issues. We hypothesized a focused, personalized approach to managing patients with NMD will improve patient adherence to PAP therapy, nocturnal oxygenation, and ventilation, as well as limit hospital admissions. Methods: 10 patients diagnosed with NMD (including muscular dystrophy, diaphragm paralysis, and scoliosis) presented to UPMC Montefiore sleep lab for daytime accommodation study with a pulmonary-sleep physician and dual-trained respiratory therapist-sleep technician. The visit included mask fitting, patient education, and initiation of PAP therapy with titration of bilevel pressure settings. Data collected included: pre- and 3-month-post nocturnal oxygen saturation and serum bicarbonate level; data download at 3 months including device usage, leak, average PAP pressures; and number of hospital admissions. Results: All 10 patients demonstrated initiation of PAP therapy with usage on 100% of days for minimum of 6 hours per night. There was improvement in average nocturnal oxygen saturation and serum bicarbonate level after visit compared to prior. 3 patients were hospitalized in 6-12 months following, none for respiratory related reasons. Conclusion: In this pilot study, an innovative daytime PAP accommodation study for patients with sleep-disordered breathing due to NMD results in excellent initiation and adherence to PAP therapy, as well as improvement in oxygenation and ventilation and minimal hospitalizations. Future studies are necessary including a larger randomized trial to demonstrate the safety and efficacy of home based NIV initiation. Support (If Any): NIH T32 HL082610-15, American Thoracic Society ASPIRE fellowship